Inhibitory Effects of an Orally Active Thromboxane A2 Receptor Antagonist, nstpbp5185, on Atherosclerosis in ApoE-Deficient Mice - Huang, Shiu-Wen; Lien, Jin-Cherng; Kuo, Sheng-Chu; Huang, Tur-Fu (Thrombosis and Haemostasis, 2018)
Thromboxane A2 (TXA2) activation of TP receptor has been shown contributing to the progression and acute complications of atherosclerosis including endothelial dysfunction, platelet hyperactivity and inflammation. Growing evidence suggests that TP receptor may represent as a therapeutic target in atherosclerosis and related cardiovascular diseases. We investigated whether nstpbp5185, an orally active TP receptor antagonist, exhibits protective effects against atherosclerotic progression. Nstpbp5185 and aspirin were orally administered daily for 12 weeks in high-cholesterol-fed ApoE-deficient mice to examine their anti-atherosclerosis effects. Total cholesterol, low-density lipoprotein cholesterol and triglycerides were slightly decreased in nstpbp5185-treated mice. However, nstpbp5185 significantly reduced neointima formation and aortic atherosclerotic lesion area. Nstpbp5185 increased serum paraoxonase 1 activity. In contrast, plasma levels of interleukin-6 and tumour necrosis factor-α were reduced in nstpbp5185-treated mice. Plasma level of TXA2 metabolite, TXB2, was lower in both aspirin- and nstpbp5185-treated mice, while the urinary 2,3-dinor-6-keto PGF1α (a PGI2 metabolite) and plasma iPF2α-III were not altered. Moreover, nstpbp5185 neither caused gastric ulceration nor affected the haemostatic response. Nstpbp5185 also inhibited U46619-induced endothelial NF-kB activation, ICAM-1 and VCAM-1 expression, as well as monocyte adhesion to endothelial cells. In conclusion, nstpbp5185 may represent as an ideal, safe and efficacious agent for preventing atherosclerotic progression through its antiplatelet, anti-inflammatory and antioxidative activities.
Keywords: ApoE-deficient mice; atherosclerosis; thromboxane A2; TP antagonist